THOMAS STAMFORD RAFFLES DI BENGKULU: POLITISI ATAU ILMUWAN? (History Department, Semarang State University and Historian Society of Indonesia, 2017)
EnglishEast India Company is not only having an authority in Java but also enjoying a long influence in Bengkulu. Thomas Stamford Raffles, an agent of EIC in Nusantara, experiences the above posts in these two strategic areas. Like in Java, Raffles has three policies in Bengkulu. Firstly, all former treaties are annulled. Secondly, authority is given to the company to administer the country according to equity, justice, and good policy. Thirdly, the cultivation of pepper is declared free, the people being at liberty to cultivate that article or not at pleasure. In addition, he finds the other strategic place to support the trade of EIC and private English in Southeast Asia. The place is called Tumasik and at present well-known as Singapore. He has also a concern on the world of flora and fauna. He works with Dr. Arnold to conduct a research on the gigantic flower of Rafflessia arnoldii and collaborates with Everard Home to study on the anatomy and biogeography of dugong. East India Company atau Kongsi Dagang Inggris ternyata bukan hanya berkuasa di Jawa tetapi juga cukup lama bercokol di Bengkulu. Thomas Stamford Raffles, salah satu agen EIC di Nusantara, merasakan kekuasaan di dua tempat strategis tersebut. Sama halnya seperti di Jawa, Raffles memiliki tiga kebijakan utama di Bengkulu. Pertama, merevisi segala perjanjian yang ada; kedua, dia mengangkat para pegawai dari rakyat pribumi dengan kesetaraan, keadilan, dan kebijakan yang tepat; dan ketiga, dia memberi kebebasan pada rakyat untuk menanam sesuatu. Selain itu, dia menemukan tempat yang sangat strategis dalam mendukung kepentingan perdagangan EIC beserta orang Inggris di Asia Tenggara. Tempat itu bernama Tumasik dan kita kenal kini sebagai Singapura. Selain itu, dia ternyata juga peduli pada tumbuhan dan hewan yang tidak pernah ditemui sebelumnya. Jika dia bekerjasama dengan Dr. Arnold ketika mengaji Rafflessia arnoldii maka bersama dengan Everard Home, dia mengaji anatomi dan bio-geografi dari dugong.